# Solve each of the following quadratic equations:x2 - 4ax - b2 + 4a2 = 0

x2 - 4ax - b2 + 4a2 = 0

x2 - 4ax – ((b)2 – (2a)2) = 0

{using a2 - b2 = (a + b)(a - b)}

x2 - (b + 2a)x + (b - 2a)x - (b + 2a)(b - 2a) = 0

x [x - (b + 2a)] + (b - 2a) [x - (b + 2a)] = 0

[x - (b + 2a)] [x + (b - 2a)] = 0

[x - (b + 2a)] = 0 or [x + (b - 2a)] = 0

x = (b + 2a) or x = - (b - 2a)

x = (2a + b) or x = (2a - b)

Hence the roots of equation are (2a + b) or (2a - b)

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Get To Know About Quadratic Formula42 mins  Quiz | Knowing the Nature of Roots44 mins  Take a Dip Into Quadratic graphs32 mins  Foundation | Practice Important Questions for Foundation54 mins  Nature of Roots of Quadratic Equations51 mins  Getting Familiar with Nature of Roots of Quadratic Equations51 mins  Quadratic Equation: Previous Year NTSE Questions32 mins  Champ Quiz | Quadratic Equation33 mins  Understand The Concept of Quadratic Equation45 mins  Balance the Chemical Equations49 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses 